2008
DOI: 10.1093/carcin/bgn109
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-8 signaling promotes androgen-independent proliferation of prostate cancer cells via induction of androgen receptor expression and activation

Abstract: The aim of our study was to assess the importance of the CXC chemokine and interleukin (IL)-8 in promoting the transition of prostate cancer (CaP) to the androgen-independent state. Stimulation of the androgen-dependent cell lines, LNCaP and 22Rv1, with exogenous recombinant human interleukin-8 (rh-IL-8) increased androgen receptor (AR) gene expression at the messenger RNA (mRNA) and protein level, assessed by quantitative polymerase chain reaction and immunoblotting, respectively. Using an androgen response e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
98
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(107 citation statements)
references
References 32 publications
6
98
1
1
Order By: Relevance
“…Indeed, the stable transfection of CXCL8 cDNA in AR-positive PCa cells reduces their dependence to androgens and reduces the growth inhibition observed in the presence of anti-androgens as bicalutamide, through CXCR1 (Araki et al 2007). On the other hand, Seaton et al (2008) reported that CXCL8 could enhance the proliferation of cancer cells, but this could not be observed in the presence of bicalutamide. Another difference with the study from Araki was that CXCL8 action occurred through CXCR2 (Seaton et al 2008).…”
Section: Do Chemokines Modulate Hormone Escape?mentioning
confidence: 92%
See 1 more Smart Citation
“…Indeed, the stable transfection of CXCL8 cDNA in AR-positive PCa cells reduces their dependence to androgens and reduces the growth inhibition observed in the presence of anti-androgens as bicalutamide, through CXCR1 (Araki et al 2007). On the other hand, Seaton et al (2008) reported that CXCL8 could enhance the proliferation of cancer cells, but this could not be observed in the presence of bicalutamide. Another difference with the study from Araki was that CXCL8 action occurred through CXCR2 (Seaton et al 2008).…”
Section: Do Chemokines Modulate Hormone Escape?mentioning
confidence: 92%
“…CXCL8 enhances in vitro growth, motility, and invasion, as well as MMP-9 and VEGF production (Reiland et al 1999, Inoue et al 2000, Seaton et al 2008. In vivo, the stable transfection of CXCL8 in PCa cells stimulates tumor growth, probably through an increased angiogenesis (Inoue et al 2000, Lee et al 2004, Araki et al 2007).…”
Section: Chemokinesmentioning
confidence: 99%
“…Consistent with this, studies in athymic mice have correlated the increased expression of IL-8 in implanted human CaP cells with increased vascularisation of the tumours and an enhanced tumourigenic and metastatic potential (Inoue et al, 2000;Kim et al, 2001). Other studies have determined the relevance of IL-8 signalling to the development of androgen-independence (Araki et al, 2007;Seaton et al, 2008), CaP cell proliferation (Murphy et al, 2005) and CaP cell survival in response to environmental and chemotherapy/biological agents (Maxwell et al, 2007;Wilson et al, 2008a, b).…”
mentioning
confidence: 85%
“…In the context of CaP, CXCL8 expression correlates with increased angiogenesis, tumourigenicity and lymph node metastasis in vivo (Inoue et al, 2000;Kim et al, 2001). We, along with others, have shown that CXCL8 signalling contributes to the transition of a disease to a castration-resistant state (Araki et al, 2007;Seaton et al, 2008). Furthermore, we have shown that CXC-chemokine signalling (including CXCL8) modulates the sensitivity of CaP cells to environmental stresses such as hypoxia and chemotherapy agents, including the DNA-damage agents oxaliplatin and etoposide Wilson et al, 2008a).…”
mentioning
confidence: 72%